Paita en una tradición de Ricardo Palma - Martos Carrera, Marco (2018)
Although preferably in Lima, the traditions of Ricardo Palma cover a large part of the national territory. The paper focuses on analyzing the one in which Manuelita Sáenz appears in his provecta age, in the port of Paita. The work is complemented by references to a recent book La Nantuca de Maintope by Miguel Cortés, a Piuran author.